The importance of the economic bid in institutional advertising campaigns: Cost vs. quality - Pérez-Seoane, Jesús; Corbacho-Valencia, Juan Manuel; Abuín-Penas, Javier (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
With more than 5,000 annual contracts and an estimated total budget of 738.3 million euros invested in institutional advertising, the public sector is the main advertiser in Spain. In its tenders, one of the aspects with the greatest impact on the award is the economic offer. The application of current regulations to ten tenders is analyzed, with special attention to abnormal low bids. The results show that the tenders favor aggressive economic offers. The best technical bid does not always win, and the impact of abnormally low bids as such is reduced.